Hubungan Motivasi dengan Kinerja Perawat Pelaksana di Ruangan Rawat Inap Rsud Dr. Rasidin Padang : Relationship between Motivation and Performance of Nurse Executives in the Inpatient Room of Rsud Dr. Rasidin Padang - Indri Ramadini; Erni Jasmita (NERS Jurnal Keperawatan, 2015)
performance achievement data dr. Rasidin Padang showed indicators of inpatient services in dr. Rasidin Padang ideal not in accordance with the standards set by the Ministry of Health. One of them can be seen from the level of utilization of the bed or Bed Occupancy Rate (BOR) in 2013 amounted to 29.50%, while the MOH ideal standard is 60% - 85%. The research objective was to determine the relationship of motivation with the performance of nurses in the inpatient room dr. Rasidin Padang in 2014. This type of research is descriptive analytic cross sectional approach. The study was conducted at room inpatient dr. Rasidin Padang from December 2013 to July 2014. All of the sampled population numbering 40 people. Data was analyzed by univariate and bivariate frequency distribution by Chi-Square. Results of the study bivariate relationship between motivation physiological needs (p = 0.012), security needs (p = 0.001), social needs (p = 0.008), needs appreciation (p = 0.010), and self-actualization needs (p = 0.001) with performance nurses. Suggested for hospital leadership to optimize the motivation of nurses so as to improve the performance of nurses in dr. Rasidin Padang.